Trillion the three-headed lion - Blade, Adam (Orchard Books London, 2015)
The peace of Avantia has been shattered by a fearsome new Beast - Trillion the Three-Headed Lion. If he is to save the kingdom, Tom must defeat Trillion and collect all the pieces of magical golden armour. Will he succeed? -- back cover